GAMBARAN PENGETAHUAN DAN POLA ASUH IBU DENGAN STATUS GIZI BADUTA DI WILAYAH KERJA PUSKESMAS MEDAN AMPLAS KOTA MEDAN - Mutia Respati; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Good nutritional status was determined by feeding  with enough nutritional content. Feeding patterns must be adapted to the nutritional needs of infants, so that children can grow and develop normally, healthy and strong. The causes of poor nutritional status is at the food on the family, parenting, health care and environmental health. These factors strongly associated with the level of education, knowledge, and skills of the family. This study aims to determine the description of knowledge and mothers parenting with baby nutritional status in Medan Amplas Health Care Medan. This study was an descriptive study with cross sectional design. Data collection was done by direct interview to mothers who include data on baby nutritional status, data on mom’s parenting (feeding, environtmental sanitation, and health care) dan data on knowledge. Data analysis was performed using univariate, bivariate, using chi-square test. These results of the research showed that most of the mother has a good category in knowledge (74,1%). Good category in mothers parenting variable as 61,1%, good category in environtmental sanitation variable as 59,3% and good category in health care variable as 63,0%. There is a relationship of knowledge with baby nutritional status, for each indicator BB/PB (p=0,017) and BB/U (p=0,005). And there is no relationship of knowledge with nutritional status TB/U (p=0,277). There is a relationship of feeding with nutritional status, for each indicator BB/PB (p=0,024) and BB/U (p=0,001). And there is no relationship of feeding with nutritional status TB/U (p=0,855). There is a relationship of environtmental sanitation with nutritional status. There is a relationship of health care with nutritional status BB/PB (p=0,010) dan BB/U (p=0,000), and there is no relationship of health care with nutritional status TB/U with (p=0,065). Based on the results, this study was expected to be increase conseling about good mother’s parenting to babies and the health care providers for motivate healt cadres to distribute information to mothers about mother’s parenting to babies. Keywords: Knowledge, Mom‘s Parenting, Baby Nutritional Status.